2011
DOI: 10.1021/es103133h
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution and Depuration Kinetics of Waterborne 14C-labeled Light PAHs in Mummichog (Fundulus heteroclitus)

Abstract: Light polycyclic aromatic hydrocarbons (PAHs) of petrogenic origin are commonly found in estuaries and coastal areas. Though they are known to be toxic to fish, little is known about their uptake and tissue distribution. This paper reports on the results of a study on uptake, elimination, and tissue distribution of three waterborne 14C-labeled PAHs in the mummichog, Fundulus heteroclitus, using whole-body autoradiography. After a 24 h exposure to 1 μCi·L(-1) of 14C-naphthalene, 14C-1-naphthol, and 14C-phenanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 62 publications
(81 reference statements)
1
15
0
Order By: Relevance
“…Given the location of fish immune organs in the vascular system, and their blood-filtering role (Press and Evensen, 1999), substantial exposure of immune organs to circulating xenobiotics is to be expected. In fact, Valdez Domingos et al (2011) showed in a toxicokinetic study on PAH distribution in medaka that a substantial fraction is distributed to the immune organs. Medaka head kidney tended to accumulate higher amounts of PAH than the spleen (Valdez Domingos et al, 2011), which is in agreement with our observation on rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the location of fish immune organs in the vascular system, and their blood-filtering role (Press and Evensen, 1999), substantial exposure of immune organs to circulating xenobiotics is to be expected. In fact, Valdez Domingos et al (2011) showed in a toxicokinetic study on PAH distribution in medaka that a substantial fraction is distributed to the immune organs. Medaka head kidney tended to accumulate higher amounts of PAH than the spleen (Valdez Domingos et al, 2011), which is in agreement with our observation on rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Valdez Domingos et al (2011) showed in a toxicokinetic study on PAH distribution in medaka that a substantial fraction is distributed to the immune organs. Medaka head kidney tended to accumulate higher amounts of PAH than the spleen (Valdez Domingos et al, 2011), which is in agreement with our observation on rainbow trout. The difference between the two immune organs might be related to their role and position in the blood system of fish: although the head kidney receives a direct supply from the dorsal aorta close to its origin, the more distant location of the spleen, as well as its function as an encapsulated plasma filter, implies a lower blood flow rate and supply.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown both in field and in laboratory studies [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. The highly vascularized immune organs and the circulating immune cells are directly exposed to absorbed contaminants and in fact they accumulate AhR-binding chemicals [ 43 , 44 ]. These facts point to the possibility that the known immunotoxic effects of PHAHs and PAHs to fish are mediated via AhR signaling in the piscine immune system.…”
Section: Introductionmentioning
confidence: 99%
“…15 The tissue distribution of 14 C-labeled Phe in Mummichog (Fundulus heteroclitus) indicated that fish liver is a major enrichment organ. 16 Exposure to 76 μg/L Phe for 96 h increased the prevalence of histopathological lesions in the liver of African catfish. 17 Unexpectedly, the Phe concentration in the peripheral venous blood of pregnant women (nonsmokers) and the cord blood of newborns can reach levels as high as 37.61 ± 0.47 and 35.32 ± 0.34 μg/L, respectively.…”
Section: Introductionmentioning
confidence: 96%